Brain-Dependent Processes Fuel Pain-Induced Hemorrhage After Spinal Cord Injury - Reynolds, Joshua A.; Henwood, Melissa K.; Turtle, Joel D.; Baine, Rachel E.; Johnston, David T.; Grau, James W. (Frontiers in Systems Neuroscience, 2019)
Pain (nociceptive) input caudal to a spinal contusion injury can undermine long-term recovery and increase tissue loss (secondary injury). Prior work suggests that nociceptive stimulation has this effect because it fosters the breakdown of the blood-spinal cord barrier at the site of injury, allowing blood to infiltrate the tissue. The present study examined whether these effects impact tissue rostral and caudal to the site of injury. In addition, the study evaluated whether cutting communication with the brain, by means of a rostral transection, affects the development of hemorrhage. Eighteen hrs after rats received a lower thoracic (T11-12) contusion injury, half underwent a spinal transection at T2. Noxious electrical stimulation (shock) was applied 6 hrs later. Cellular assays showed that, in non-transected rats, nociceptive stimulation increased hemoglobin content, activated pro-inflammatory cytokines and engaged signals related to cell death at the site of injury. These effects were not observed in transected animals. In the next experiment, the spinal transection was performed at the time of contusion injury. Nociceptive stimulation was applied 24 hrs later and tissue was sectioned for microscopy. In non-transected rats nociceptive stimulation increased the area of hemorrhage and this effect was blocked by spinal transection. These findings imply that the adverse effect of noxious stimulation depends upon spared ascending fibers and the activation of rostral (brain) systems. If true, stimulation should induce less hemorrhage after a severe contusion injury that blocks transmission to the brain. To test this, rats were given a mild, moderate, or severe, injury and electrical stimulation was applied 24 hrs later. Histological analyses of longitudinal sections showed that nociceptive stimulation triggered less hemorrhage after a severe contusion injury. The results suggest that brain-dependent processes drive pain-induced hemorrhage after spinal cord injury.